A Study on Pros and Cons of ChatGPT in Education on Students’ Perspective - B. Pavithra; S. Pavithra Arasi; B. Keerthana (Journal of Integrated Marketing Communications and Digital Marketing (p-ISSN: 3107-9172), 2024)
Artificial intelligence (AI) models, such as ChatGPT (Chat Generative Pre-Trained Transformer), have gained prominence across various fields, including education research and publishing. This review article examines the advantages and disadvantages of using ChatGPT in education. With the rise in technology, chatbots have become more prevalent as AI enables the conversion of natural languages. This study explores the integration of ChatGPT, an AI-driven chatbot developed by OpenAI, in educational settings, focusing on its impact on student satisfaction. The research employs a descriptive methodology, utilizing convenience sampling to gather data from 112 respondents in Coimbatore city. Findings reveal that 52.7% of students find ChatGPT convenient, while 63.3% express satisfaction or high satisfaction with its use. However, challenges persist, particularly regarding the Chabot’s lack of human intelligence and occasional inaccuracies, which are ranked as the primary difficulties users face. The study underscores the importance of balancing AI assistance with traditional learning methods, advocating for responsible usage to enhance educational outcomes and foster independent thinking. Ultimately, the findings highlight ChatGPT’s potential as a valuable educational tool while calling for awareness of its limitations.